E-theses and the Nordic E-theses Initiative. The Impact of the Joint Work on the Role of the Library - Müller, Eva (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
The concept of collaborative development and cooperation within libraries when it comes to the development of technical solutions, policies and practices supporting electronic publishing is becoming more common today. There are numbers of possible approaches how to proceed. I will share the experience based on working with other libraries within a consortium. My intention is to contribute to understanding the advantages of a community system development and the necessary organizational framework being set up to support it. I’ll introduce the DiVA project and the DiVA publishing system developed by the Electronic Publishing Centre at Uppsala University Library. DiVA provides a good example of how electronic publishing is possible to carry out within a university library organisation and how a strategy of collaborative development between a numbers of institutions can work in practice.